Balkans, Germany and Austria-Hungary on the eve and during the first word war in Estonian national historiography of the interwar period - Улунян, Артём (Balcanica Posnaniensia. Acta et studia, 2012)
The article gives an overview of approaches that has been developed in interwar Estonian historiography of world affairs in the Balkans on the eve and during WWI. In that time the progress in the researchers of world history has been noticed in Estonian national historical science. Despite scarcity in their number and predominance among them of those who has been making only first steps in science, or so-called „beginners”, Estonian scholars have displayed certain achievements in this field. Young Estonian authors have focused their efforts on studies of German foreign policy combinations, internal weakness of the Austro-Hungarian Empire, strengthening of the national movements in Dual Monarchy and particular territorial interests of Great Powers. So-called young generation of the scholars has been influenced on the side of their elder „mentors”, specialists in world history, have defined Balkans as the fulcrum of WWI. The preponderance of German factor in their writings should be explained with the fact that Germany has been playing strong and active role in many spheres of Estonian life for a long time span. In some ways, it affected also sociological approach to analysis of world affairs. Both young and elder Estonian historians shared of socially oriented ideas of independent nationhood, which served as basic principal of their explanations of the international events and which has been seriously influenced by Estonia’s domestic situation.